Mutation Studies of 31 Highly Mutated Y-chromosomal Short Tandem Repeat Systems in the Han Population of Northern China - Shicheng Hao; Jinghan Chen; Hang He; Li Yuan (Wolters Kluwer Medknow Publications, 2024)
A six-color fluorescent multiplex amplification system for 31 Y-chromosomal short tandem repeats (Y-STRs) (DYS19, DYS390, DYS391, DYF399S1, DYF404S1, DYS439, DYS444, DYS449, DYS452, DYS456, DYS458, DYS460, DYS481, DYS508, DYS513, DYS516, DYS518, DYS543, DYS547, DYS549, DYS552, DYS557, DYS570, DYS576, DYS612, DYS622, DYS626, DYS627, DYS630, DYS635, and Y-GATA-A10) was developed for investigating the mutation rates of 31 highly mutated Y-STR genes in the Han population of northern China. The mutation rates of the 31 highly mutated Y-STRs were calculated using the father-son pair study method after typing 526 Northern Han father-son pairs with this system. Statistically, 148 Y-STR mutations were found, with mutation rates ranging from 0 (95% confidence interval [CI] 0 to 9.0 × 10−3, DYS622) to 7.0 × 10−2 (95% CI 5.1 × 10−2 to 9.7 × 10−2, DYF399S1). Out of these, 126 father-son pairs were successfully identified, with a distinction rate of 24.0% (95% CI 20.4%-27.9%). The ability of the 31 highly mutated Y-STRs to distinguish closely related males from the same paternal lineage in the Northern Han population is extremely valuable for criminal investigations and other purposes.